2009
DOI: 10.1037/a0014877
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cognitive theory: A joint modeling approach using responses and response times.

Abstract: In current psychological research, the analysis of data from computer-based assessments or experiments is often confined to accuracy scores. Response times, although being an important source of additional information, are either neglected or analyzed separately. In this article, a new model is developed that allows the simultaneous analysis of accuracy scores and response times of cognitive tests with a rule-based design. The model is capable of simultaneously estimating ability and speed on the person side a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 89 publications
2
74
0
Order By: Relevance
“…First, it is particularly appealing in the context of Borsboom's (2006) view that the fact that measurement models lack substantive foundation is the main reason psychometrics has had a limited impact. That is, although the analysis of choice response time data in a hierarchical framework has already been addressed in the psychometric literature (Klein Entink, Kuhn, Hornke, & Fox, 2009;van der Linden, 2007), our use of a popular process model such as the diffusion model is novel. At the same time, of course, the process interpretation limits the applicability of the present approach, because one is now required to assume that the process assumptions are not violated.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is particularly appealing in the context of Borsboom's (2006) view that the fact that measurement models lack substantive foundation is the main reason psychometrics has had a limited impact. That is, although the analysis of choice response time data in a hierarchical framework has already been addressed in the psychometric literature (Klein Entink, Kuhn, Hornke, & Fox, 2009;van der Linden, 2007), our use of a popular process model such as the diffusion model is novel. At the same time, of course, the process interpretation limits the applicability of the present approach, because one is now required to assume that the process assumptions are not violated.…”
Section: Discussionmentioning
confidence: 99%
“…Klien Entink et al [114] proposed to marry an LLTM approach with the hierarchical modeling approach, as discussed in Section 6.2 [95]. They also employed a full Bayesian framework using Markov Chain Monte Carlo methods to estimate the model.…”
Section: Cognitive Componentsmentioning
confidence: 99%
“…A limitation of the two-step approach is that it fails to model the relationship between responses and response times [114]. Klien Entink et al [114] proposed to marry an LLTM approach with the hierarchical modeling approach, as discussed in Section 6.2 [95].…”
Section: Cognitive Componentsmentioning
confidence: 99%
“…Empirical examples of Klein Entink, Fox, and van der Linden (2009) showed that higher-ability test takers tended to work at a slower speed than lower-ability test takers. Klein Entink, Kuhn, Hornke, and Fox (2009), Roberts and Stankov (1999), and van der Linden and Fox (2015) also have reported a negative correlation between ability and speed in their empirical examples.…”
Section: Introductionmentioning
confidence: 99%